Perancangan Pengurangan Lead Time Produksi pada Perusahaan Produksi Mebel - I Dewa Made Tastra Asrama; I Nyoman Sutapa (Jurnal Titra, 2021)
This furniture production company has a problem with it’s slow production lead time. The company was given a target by the customer to complete the product within 9 days, but the product was completed in 11,59 days. The method used is value stream mapping, fishbone diagram, improvement using brainstorming method, and control using administrative control. The root cause of the slow production lead time is in the welding process that there’s no Standard Operating Procedure (SOP) and in the weaving process due to some workers unskilled in weaving. The proposal from this design is to make welding SOPs and provide training to slow workers so they can work faster.